Pengaruh Alokasi Dana Desa terhadap Pertumbuhan Ekonomi, Indeks Pembangunan Manusia serta Kemiskinan di Kabupaten Bima - M. Rimawan; Fenny Aryani (Universitas Pendidikan Ganesha, 2019)
The Economic performance of a region can be seen from the of Gross Regional Domestic Revenue or economic growth. The economic growth of the regions has an important role in creating prosperity, increasing the standard of living and providing employment. Village fund Allocation is as a stimulant fund to encourage and finance village government programs that are supported by community participation in carrying out government activities, development and community empowerment. Although Village fund Allocation in the past 5 years has tends to fluctuate, human development index increases and poverty fluctuates. Thus the main objective of this study is to analyzen the impact of Village fund Allacoation on economic growth. Human development index and Poverty in Bima Regency. The Analytical method used is a quantitative research method using the Warp PLS statistical tool. The result of analysis show that the variable Allocation of Village funds has a positive effect on economic growth, the human development index while does not affect poverty